Analysis of Success Factors for YouTube Niches - Vladimir Ciubotaru (Emerging Frontiers Library for The American Journal of Management and Economics Innovations, 2025)
The methodology introduced in this article combines a comprehensive model for assessing both market demand and saturation, an adaptive content-design principle based on the 50/40/10 formula, the use of hybrid video-production structures, and experimental hypothesis testing on a dataset of 157 channels. This integrative approach accommodates varied conditions and heterogeneous strategy formats. The study simultaneously identifies fundamental obstacles faced by novice creators—most notably the confirmation effect and survivorship bias—and proposes effective instruments for neutralizing these psychological traps, thereby fostering more informed and balanced decision-making. Empirical analysis indicates sustained audience growth of 8–12 % per month, viewer retention between 55 % and 65 %, and click-through rates of up to 9 %, all of which clearly outperform traditional approaches and underscore the practical significance of the proposed concept. The work is intended for professionals and researchers in digital promotion who design competitive video projects within YouTube’s dynamic, saturated media environment, and the findings possess high practical value and universal applicability across thematic segments.